Studying Brand Preference And Brand Loyalty Of Iranian Students Living In Malaysia - Salehi, Abuzar (2008)
This study examines the determinants of consumer's brand preference and brand loyalty among Iranian students living in Malaysia with significant emphasis on restaurant industry.